2015
DOI: 10.1016/j.edurev.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Automated, adaptive guidance for K-12 education

Abstract: A B S T R A C TThis paper distinguishes features of automated adaptive guidance used in K-12 instructional settings and recommends directions for design. We use meta-analysis to synthesize 24 independent comparisons between automated adaptive guidance and guidance provided during typical teacher-led instruction, and 29 comparisons that isolate the effects of specific adaptive guidance design features in computer-based instruction. We find automated adaptive guidance to be significantly more effective than guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 50 publications
1
25
0
3
Order By: Relevance
“…The learning outcomes of students for each teacher align with previous research that illustrates the importance of teacher guidance (Gerard et al, ; McNeill & Krajcik, ; Ruiz‐Primo & Furtak, ). In a review of inquiry‐supported instruction, Furtak, Seidel, Iverson, and Briggs () found learning gains for inquiry based curricula, but these gains tended to be greater when students were supported with teacher guidance.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The learning outcomes of students for each teacher align with previous research that illustrates the importance of teacher guidance (Gerard et al, ; McNeill & Krajcik, ; Ruiz‐Primo & Furtak, ). In a review of inquiry‐supported instruction, Furtak, Seidel, Iverson, and Briggs () found learning gains for inquiry based curricula, but these gains tended to be greater when students were supported with teacher guidance.…”
Section: Discussionsupporting
confidence: 80%
“…In WISE, teacher's guidance prompts and scores reflect engagement with student work (Gerard, Matuk, McElhaney, & Linn, ). The teachers demonstrated nuanced approaches in their use of the guidance tools (see Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, given that teachers' time is an increasingly valuable resource, several adaptive software agents have recently been developed to support teachers on specific tasks and that adapt the guidance to students' characteristics. While Belland et al (2016) found no added effect of limited adaptive scaffolding over static scaffolding, intelligent tutoring systems (Nye et al, 2014), adaptive environments (Durlach and Ray, 2011;Vandewaetere et al, 2011), and automated feedback (Gerard et al, 2015(Gerard et al, , 2016 have all shown promising results. The common-sense conclusion appears to be that the more guidance is adapted to the individual student, the better the guidance-and thus the student-performs.…”
Section: Adaptive and Automated Scaffoldingmentioning
confidence: 99%